Graph theoretical network analysis, in silico exploration, and validation of bioactive compounds from Cynodon dactylon as potential neuroprotective agents against α-synuclein - Raja Rajeswari Rajeshkumar; Banoth Karan Kumar; Pavadai Parasuraman; Theivendren Panneerselvam; Krishnan Sundar; Damodar Nayak Ammunje; Sureshbabu Ram Kumar Pandian; Sankaranarayanan Murugesan; Shanmugampillai Jeyarajaguru Kabilan; Selvaraj Kunjiappan (BioImpacts, 2022)
Introduction: Parkinson's disease (PD) is a chronic, devastating neurodegenerative disorder marked by the death of dopaminergic neurons in the midbrain's substantia nigra pars compacta (Snpc). In alpha-synuclein (α-Syn) self-aggregation, the existence of intracytoplasmic inclusion bodies called Lewy bodies (LBs) and Lewy neurites (LNs) causes PD, which is a cause of neuronal death. Methods: The present study is aimed at finding potential bioactive compounds from Cynodon dectylon that can degrade α-Syn aggregation in the brain, through in silico molecular docking investigations. Graph theoretical network analysis was used to identify the bioactive compounds that target α-Syn and decipher their network as a graph. From the data repository, twenty-nine bioactive chemicals from C. dactylon were chosen and their structures were retrieved from Pubchem. On the basis of their docking scores and binding energies, significant compounds were chosen for future investigation. The in silico prediction of chosen compounds, and their pharmacokinetic and physicochemical parameters were utilized to confirm their drug-likeness profile. Results: During molecular docking investigation the bioactive compounds vitexin (-7.3 kcal.mol-1) and homoorientin (-7.1 kcal.mol-1) showed significant binding energy against the α-Syn target protein. A computer investigation of molecular dynamics simulation study verifies the stability of the α-Syn-ligand complex. The intermolecular interactions assessed by the dynamic conditions indicate that the bioactive compound vitexin has the potency to prevent α-Syn aggregation. Conclusion: Interestingly, the observed results indicate that vitexin is a potential lead compound against α-Syn aggregation, and in vitro and in vivo studies are warranted to confirm the promising therapeutic capability.